2019
DOI: 10.1002/cam4.2148
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic bacteria to combat cancer; current advances, challenges, and opportunities

Abstract: Successful treatment of cancer remains a challenge, due to the unique pathophysiology of solid tumors, and the predictable emergence of resistance. Traditional methods for cancer therapy including radiotherapy, chemotherapy, and immunotherapy all have their own limitations. A novel approach is bacteriotherapy, either used alone, or in combination with conventional methods, has shown a positive effect on regression of tumors and inhibition of metastasis. Bacteria‐assisted tumor‐targeted therapy used as therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
153
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(156 citation statements)
references
References 150 publications
0
153
0
3
Order By: Relevance
“…Bacteria–host interactions also trigger in vivo potent host immune responses. These bacterial‐driven immune responses have been exploited from long in antitumour therapies (Kramer, Masner, Ferreira, & Hoffman, ; Sedighi et al, ) but less is known about the exact mechanisms that finally triggered antitumour activity. Besides classical forms of tumour treatments such as radiation and chemical therapy, an emerging field, revolutionising oncology, regards the use immunotherapies, allowing the treatment of tumours with otherwise very bad prognosis (Chen & Mellman, ).…”
Section: From Cellular Microbiology To Clinical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteria–host interactions also trigger in vivo potent host immune responses. These bacterial‐driven immune responses have been exploited from long in antitumour therapies (Kramer, Masner, Ferreira, & Hoffman, ; Sedighi et al, ) but less is known about the exact mechanisms that finally triggered antitumour activity. Besides classical forms of tumour treatments such as radiation and chemical therapy, an emerging field, revolutionising oncology, regards the use immunotherapies, allowing the treatment of tumours with otherwise very bad prognosis (Chen & Mellman, ).…”
Section: From Cellular Microbiology To Clinical Applicationsmentioning
confidence: 99%
“…Similarly, it has been shown that some bacteria have a preference to grow in the hypoxic/inmunosupressive ambient of solid tumours (like Salmonella spp, L. monocytogenes or Clostridium spp) and this ability could be combined with cytotoxic toxins to kill target cells (Sedighi et al, ). There is an increasing effort to engineer safe bacteria to improve the selective elimination of the tumour, which in addition could increase the ‘immunological death’ of tumour cells, liberating danger signals, activating the immune system, and therefore enhancing the antitumor effect of the bacteria‐based antitumor treatment (Galluzzi, Buqué, Kepp, Zitvogel, & Kroemer, ).…”
Section: From Cellular Microbiology To Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,4,7] Moreover, bacterial injections can induce necrotic cells to generate heat shock proteins, such as HSP70, resulting in the maturation of antigen presenting cells (APCs), which participate extensively in antitumor activities. [8,9] The antitumor response of bacteria is also likely to be associated with the adjuvant effect of their microbial-associated molecular pattern molecules, including fimbriae and lipopolysaccharide. [9,10] Although BMTT is regarded as effective, the use of bacteria in antitumor treatment has never become a routine clinical practice because of the risk that bacterial toxins cause infections.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, bacterial infection activates host immunity and promotes a therapeutic effect [12,13]. Salmonella is bacteria with multiple anti-tumor functions, including tumor targeting, intratumoral penetration, direct tumor killing, anti-angiogenic, and immune activation [14][15][16][17]. Phase I clinical trials using salmonella have been allowed by the United State Food and Drug Administration (FDA) for advanced cancer patients [18][19][20].…”
Section: Introductionmentioning
confidence: 99%